Modelling organisational citizenship behaviour for secondary school teachers: The associating factors of principal support, organisational justice, meaningful work and professional commitment / Nurharani Selamat - Selamat, Nurharani (Institute of Graduate Studies, UiTM, 2018)
As a country that aims to achieve high-income and developed nation status by 2020, Malaysia is in dire needs to improve the quality of education. Teachers are seen as key players in fulfilling the demands of high quality education especially teachers who are willing to demonstrate extra-role behaviour which is termed as organisational citizenship behaviour (OCB). Despite the cruciality of OCB in determining quality of education, scholars could not find a consensus on the best dimensions to constitute teachers’ OCB. Furthermore, research on teacher’s OCB remains scarce due to the lack of awareness regarding the contributions of OCB to enhance school effectiveness as compared to business organisations. Thus, this study has attempted to test and validate the alternative model for teachers’ OCB, known as The Teacher’s Triangular OCB Model. Moreover, drawing on social exchange theory and psychological ownership theory, and supported by organisational citizenship behaviour theory, organisational justice theory, social support theory, professional commitment theory, and workplace spirituality theory, this study aims to examine the effect of principal support, organisational justice, meaningful work, and professional commitment on OCB among secondary school teachers. A quantitative approach and cross-sectional survey strategy was employed as the research method of this study…